Health-Related Quality of Life Assessment of COVID-19 Patients: A Hospital-Based Study - Marlina Rajagukguk (CV. Inara, 2025)
Background: Covid-19 causes various symptoms in patients, ranging from manifestationsdiseasemild to severe illness andevendeath. This study assessed quality of life (the health-related quality of life/HRQOL)relatedhealthCovid-19 patientswithusing primary data from confirmed cases inCentral HospitalEthiopia South. Method : This study used a facility-based cross-sectional study design and conducted the study at the Covid-19 treatment center of Bokoji Hospital. A structured questionnaire and the EQ-5D-3L scale were used to collect data for analysis. HRQOL results measured by the EQ-5D-3L tool were converted into health status utilities. (HSU) usestariff serviceZimbabwe. The mean health utility index and HSU visual analogue scale across various sociodemographic and clinical characteristics were compared using the Mann–Whitney U test or the Kruskal–Wallis test. Done Multiple linear regression was used to examine factors associated with HSU scores simultaneously. Data were analyzed using STATA version 15. Results:The overall mean HSU score of the EQ-5D was 0.688 (SD: 0.285), and the median was 0.787 (IQR 0.596, 0.833). The mean HSU score of the visual analog scale was 0.69 (SD: 0.129), with a median of 0.70 (IQR 0.60, 0.80).Patientthose receiving dexamethasone and intranasal oxygen supplements, those with comorbidities, those aged over 55 years and those hospitalized for more than 15 days had significantly lower HSU scores thanother patients(p<.001). Conclusion:COVID-19 has substantially impaired the HRQOL of patients in Ethiopia, particularly among the elderly and those with comorbidities. Therefore, clinical follow-up and psychological care should be encouraged for these groups.